PENGARUH KECEMASAN BERKOMPUTER DAN KEMAMPUAN INDIVIDUAL SERTA PENGARUHNYA TERHADAP MINAT MAHASISWA AKUNTANSI MENGGUNAKAN SOFTWARE AKUNTANSI (Pada Mahasiswa Akuntansi Fakultas Ekonomi Universitas Islam Sumatera Utara) - Sri Rahayu; Zufrizal . (Universitas Islam Islam Sumatera Utara, 2019)
The research aims to test partially and simultaneously the effect of computer anxiety, and individual ability on student interest using accounting software for Accounting Students at UISU FE. This study is included in the study of surveys in a population. The population in this study were 258 S1 Accounting students of 2017 and 2016 UISU FE who were still active in lectures who had been or were taking courses in Accounting Information Systems and Accounting Computers. The questionnaire was tested for its validity and reliability before conducting research data collection. The test tool used in this study is to use the analysis prerequisite test which includes linearity test and classic assumption test which includes multicollinearity test and heteroscedasticity test. The data analysis method used is simple regression analysis and multiple regression analysis. The results of this study are: (1) There is a significant effect of computerized anxiety on the interest in using accounting software, (2) There is no significant effect of individual abilities on interest in using accounting software, and (3) There is a significant influence of computer anxiety and individual abilities on student interest using accounting software.